(untitled) (Physical Education, Health and Social Sciences, 2026)
Rice (Oryza sativa L.), a staple providing calories for over half the global population, faces escalating threats from abiotic stresses salinity (affecting 20% of irrigated lands), drought, and heavy metal contamination (As, Cd, Pb) projected to cause 50–70% yield losses amid climate change and a 2050 population surge to 10 billion. Conventional breeding and genetic engineering face limitations in conferring multi-stress tolerance due to polygenic traits and regulatory hurdles. This review elucidates the pivotal role of plant growth-promoting bacteria (PGPB) as sustainable bio-tools for enhancing rice resilience. PGPB employ direct mechanisms including phytohormone production (IAA, gibberellins, cytokinins), nutrient mobilization (N-fixation, P/Zn-solubilization, siderophores), and ACC deaminase-mediated ethylene reduction to sustain root architecture, photosynthesis, and nutrient uptake. Indirect pathways involve pathogen suppression via antimicrobials (HCN, VOCs) and induced systemic resistance (ISR) through JA/ethylene signaling, boosting antioxidants (phenolics, flavonoids) and ROS scavenging. Under salinity, PGPB modulate ion transporters (SOS, HKT, NHX, H+-ATPase) to maintain low Na+/K+ ratios and osmotic balance via exopolysaccharides and osmoprotectants. Drought tolerance is augmented by improved water retention, stomatal regulation, and ABA signaling, while heavy metal detoxification occurs through biosorption, methylation (As), and chelation, reducing grain accumulation. Synergistic PGPB consortia (Bacillus, Pseudomonas, Azospirillum) yield superior outcomes, with field trials showing 15–50% yield gains. Challenges include strain specificity, environmental variability, and commercialization barriers, yet PGPB integration with agronomic practices offers eco-friendly pathways for climate-resilient rice production.